2018
DOI: 10.1021/acs.jpcc.8b05744
|View full text |Cite
|
Sign up to set email alerts
|

Au–Rh Surface Structures on Rh(111): DFT Insights into the Formation of an Ordered Surface Alloy

Abstract: Surface alloying is an important technique to change their chemical properties. In this study, by employing density functional theory (DFT) calculations, the atomic arrangements and energetics of an extensive set of Au-Rh structures in a confined (2×1) surface cell on a Rh(111) substrate are investigated. An ordered surface alloy layer composed of 50% Au and 50% Rh is identified as the energetically favored structure, which corresponds to a configuration proposed previously based on scanning tunneling microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
4
0
2
Order By: Relevance
“…The remarkable propensity of Au atoms to migrate towards the surface notwithstanding its small diffusion coefficients [47] (it was estimated in the order of 10 −17 cm 2 /s) suggests a strong tendency to form segregated phases with Rh preferably confined within a gold shell, in line with what observed in the previously discussed simulations where the seed was made of Rh atoms. Despite the general consensus in reputing the Rh@Au core‐shell arrangement as the most stable for AuRh arising from computational inspections, [28–31,48] this is the first time the arising of this chemical order is directly observed with atomistic accuracy in such small nanoclusters through MD simulations. This tendency to form alloys with this specific chemical ordering can be justified by the higher cohesive of Rh atoms compared to Au, which naturally try to rearrange in order to minimise the exposed surface and saturate all pending bonds.…”
Section: Resultsmentioning
confidence: 90%
“…The remarkable propensity of Au atoms to migrate towards the surface notwithstanding its small diffusion coefficients [47] (it was estimated in the order of 10 −17 cm 2 /s) suggests a strong tendency to form segregated phases with Rh preferably confined within a gold shell, in line with what observed in the previously discussed simulations where the seed was made of Rh atoms. Despite the general consensus in reputing the Rh@Au core‐shell arrangement as the most stable for AuRh arising from computational inspections, [28–31,48] this is the first time the arising of this chemical order is directly observed with atomistic accuracy in such small nanoclusters through MD simulations. This tendency to form alloys with this specific chemical ordering can be justified by the higher cohesive of Rh atoms compared to Au, which naturally try to rearrange in order to minimise the exposed surface and saturate all pending bonds.…”
Section: Resultsmentioning
confidence: 90%
“…When we discuss the catalytic behavior of bimetallic catalysts, we should consider that the Au-Rh interaction on titanates (Au-Rh/TiONW) produces a core-shell structure similar to the well defined TiO 2 (110). In previous works, it was demonstrated with STM, XPS and LEIS measurements that Rh core-Au shell clusters can be formed on TiO 2 (110) if Au is post deposited by physical vapor deposition (PVD) on the substrate containing Rh clusters [91][92][93][95][96][97]. The surface composition of Au-Rh clusters on titanate nanocomposite was also investigated by LEIS [89].…”
Section: Co 2 Hydrogenation On Titania and Titanate Supported Rhmentioning
confidence: 99%
“…It was demonstrated that epitaxy between two metals may yield heterostructures with novel properties in terms of structure and reactivity. , For example, by epitaxial overgrowth of a second metal, ordered and unordered mixed alloy nanoparticles often with core–shell structure can be created . The lattice mismatch between the two metals plays a critically important role in the overgrowth process of these nanoparticles and metal layers, which also has to be considered when preparing, for example, metal carbides using the iron deposition method.…”
Section: Introductionmentioning
confidence: 99%